Financial Attitude and Spiritual Intelligence as Predictors of Financial Management Behavior in LAZISMU Employees Muhammadiyah Center - Amri, Andi; Gultom, Mitra Sami (Universitas Siliwangi, 2023)
Introduction to The Problem: Indonesian people have a low level of financial management, because in general they have not been able to place which ones are needs and which ones are desires.Purpose/Objective Study: This study aims to see the influence of financial attitude on financial management behavior in employees of LAZISMU Muhammadiyah Center and also the influence of spiritual intelligence on financial management behavior on employees of LAZISMU Employees Muhammadiyah Center.Design/Methodology/Approach: The type of research used is quantitative with a causality approach. The population in this study was all employees of LAZISMU Muhammadiyah Center, so that as many as 55 respondents were obtained after sampling with purposive sampling. Data analysis techniques use multiple linear regression.Findings: The results showed that Financial Attitude has a positive and significant effect on Financial Management Behavior and similarly Spiritual Intelligence also has a positive and significant effect on Financial Management Behavior. The results of this study on an R2 basis had a considerable influence, namely 70.6% while the remaining 29.4% of other factors outside this study.